Augmented reality board game in promoting financial literacy among Malaysia secondary school students - Khoo, Yin Yin; Siraj, Saedah; Mohd Noor, Mohd Asri; Yoke Seng, Wong; Ramdan, Mohamad Rohieszan; Abd. Hadi, Fatimah Salwah (Institute of Advanced Engineering and Science, 2025)
About two third of working millennials have not saved and only 5% of millennials have enough saving. This study aimed the aim of the study is to promote financial literacy among secondary students using board games. Besides that, this study also focuses to enhance students’ financial planning skills after using the board game. On the other hand, this study also investigates whether there is any gender difference between male and female students. The study employs the survey design. A total of 235 secondary school students aged between 15-16 years old from three different states in Malaysia was taken as samples in this study. A board game with augmented reality named FinPlan was used in this study. The study found that there was no difference between test score of financial literacy among male and female. However, there were significant between personal financial planning, practices, and interest towards financial literacy. Female students were outperformed than male students in each criteria. Conceptually, this study contributes to the development of the board game in financial literacy and give insight to the potential of mobile application with augmented reality. This learning method allows students to learn the daily situation that happen such as rewards, penalties and life event. It also brings a message to students, many daily activities that we need to spend money rather than saving the money; therefore, the students must plan the money properly.